A smoothing strategy for hybrid storage based on EEMD and two-level fuzzy control. Issue 1 (1st October 2022) - Deng, Hao; Zhang, Yingchao; Li, Cui; Li, Haiming; Liu, Peng; Xu, JiaFeng
Abstract: Wind power has the characteristics of randomness and intermittence. A smoothing control theory for hybrid Energy storage equipment (HESS) using Ensemble Empirical Mode Decomposition (EEMD) to allot power and two-level fuzzy control theory to adjust the power of the Energy storage equipment is proposed. EEMD can decompose wind power, the battery is used to weaken the long-term power fluctuation, and the super capacitor is used to weaken the short-term power fluctuation. Using HESS can improve the service life of Energy storage equipment.